The crystal structure of 4-(3-bromophenyl)pyrimidin-2-amine, C10H8BrN3 - Khan Arshad; Usman Rabia; Khan Amjad; Refat Moamen S.; Alosaimi Abeer M.; Bakare Safyah B.; Alghamdi Mohammed T. (Zeitschrift für Kristallographie - New Crystal Structures)
C10H8BrN3, orthorhombic, Pbca (no. 61), a = 7.214(3) Å, b = 12.735(6) Å, c = 21.305(9) Å, V = 1957.3(15) Å3, Z = 8, R gt(F) = 0.0353, wR ref(F 2) = 0.0808, T = 293 K.